EVALUASI KEBIJAKAN PENYELENGGARAAN REKLAME DI KOTA SEMARANG - Argiannata Gitarus; Kismartini Kismartini (Journal of Public Policy and Management Review, 2016)
Semarang city as a capital of Central Java Province is located in a strategic location and supported by the availability of facilities and infrastructures. Therefore Semarang became the center of economic growth in the region of Central Java, especially in the procurement of goods and services. Increased of Community’s needs resulted in the promotion of goods and services competition with variuos kinds of media one of which is advertisement. A lot of billboards constructed not according to the rules in any places so that interfere public order. To manage the growth of billboard in Semarang, government makes Regulation No 14 Year 2012 about Implementation of Advertising, which aims to improve the control and oversight of the advertisements and improve services to the public openly and fairly. The research method used is desciptive qualitative, The data collected with interview literature review and observation. This research subject is department PJPR, Satpol PP Semarang and advertisement agency. The Purpose of this research is to evaluate implementation of advertisement policy in Semarang City and reveal supporting and obstacle factor of advertisement policy. This research is connecting between Perda No 14 Tahun 2012 about Implementation of Advertising with evaluation criteria according to William N. Dunn which is effectiveness, efficiency, adequacy, grading, responsiveness and accuracy. The results of this research indicate that implementation of advertisement in Semarang that have not been implemented optimally. There were many abuses by advertising agency that the placement of billboard was not according to the rules and interfere the public facilities. Limited human resources. Less intensity of coordination between the implementers.